2005
DOI: 10.1051/kmae:2005015
|View full text |Cite
|
Sign up to set email alerts
|

Native and Alien Decapoda Species in Hungary:distribution, Status, Conservation Importance

Abstract: Three native (Astacus astacus, Astacus leptodactylus, Austropotamobius torrentium) and three alien (Orconectes limosus, Pacifastacus leniusculus, Eriocheir sinensis)Decapoda species have been found in Hungary so far. A. astacus is the most widespread Decapoda species in Hungary. A. leptodactylus might be considered as the least studied. The distribution of A. torrentium in Hungary is restricted to mountain streams with occasional data on its presence in the adjacent section of the River Danube. The indigenous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…Since 2003 it has been found at several sites along the Danube River and its tributaries or adjacent channels (Figure 1). The presence of O. limosus in the Hungarian and Serbian parts of the Danube River was confirmed in several studies (Karaman and Machino, 2004;Puky et al, 2005;Pavlovič et al, 2006;Puky and Schad, 2006), some of which have emphasized the fast colonization rate of this species in its downstream migration along the Danube River (13-16 km·yr −1 ; Puky and Schad, 2006). In Serbia, the spiny-cheek crayfish was recorded in 2002 in the Danube River near Apatin, which is only 10 km upstream of the locality of the first record in Croatia.…”
Section: > Spiny-cheek Crayfish (Orconectes Limosus)mentioning
confidence: 66%
See 1 more Smart Citation
“…Since 2003 it has been found at several sites along the Danube River and its tributaries or adjacent channels (Figure 1). The presence of O. limosus in the Hungarian and Serbian parts of the Danube River was confirmed in several studies (Karaman and Machino, 2004;Puky et al, 2005;Pavlovič et al, 2006;Puky and Schad, 2006), some of which have emphasized the fast colonization rate of this species in its downstream migration along the Danube River (13-16 km·yr −1 ; Puky and Schad, 2006). In Serbia, the spiny-cheek crayfish was recorded in 2002 in the Danube River near Apatin, which is only 10 km upstream of the locality of the first record in Croatia.…”
Section: > Spiny-cheek Crayfish (Orconectes Limosus)mentioning
confidence: 66%
“…Literature data gathering included data from neighboring countries in the region, namely Slovenia, Serbia and Hungary (Pöckl, 1999;Bertok et al, 2003;Puky et al, 2005;Govedič, 2006;Govedič et al, 2007;Pavlovič et al, 2006;Puky and Schád, 2006;Veenvliet, 2006), as the presence of NICS in Croatia is mainly the consequence of their dispersal through large rivers of the region. Fieldwork was performed along the Drava River catchment from September 2007 to August 2009.…”
Section: > Research Methodsmentioning
confidence: 99%
“…There is a certain likelihood that the spiny-cheek crayfish may naturally reach lower reaches of the Morava by upstream migration from the Danube. Not only this species is present in the Danube in Austria (PÖCKL, 1999) and in Hungary where it is actively spreading (PUKY, 2000;PUKY et al, 2005), but it has been already sparsely found directly in the lower reaches of the Morava in Austria, approximately 30 km downstream from the Czech border (PÖCKL and PEKNY, 2002). Other potential sources from where this species might be transferred to the Morava watershed are located in watersheds of the Odra (Oder) and the Wisla (Vistula) in Poland (KOZÁK et al, 2004), or of the Elbe.…”
Section: Discussionmentioning
confidence: 99%
“…The relevant legislation relating to freshwater crayfish varies across Europe (Vigneux et al, 2002, Edsman andSmietana, 2004) and within states (Puky et al, 2005), and its efficacy has been questioned (Holdich and Pöckl, 2005). Variable controls in trans-national catchments, notably the Danube system, are particularly problematic in regard to the spread of species (Puky et al, 2005;Pârvulescu et al, 2009), and European legislation is not strong enough in this regard. There are also problems of enforcement, particularly in internet based trade.…”
Section: > Comments On Some Other Countriesmentioning
confidence: 99%